2018
DOI: 10.1136/practneurol-2018-001986
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral catheter angiography and its complications

Abstract: Catheter-based angiography is an important but invasive procedure in vascular neurology. It is used mainly for diagnosis and for planning treatment in patients with a suspected underlying vascular abnormality. It is often performed as a semiurgent, planned investigation or linked to an interventional procedure. Cerebral angiography provides high-resolution, three-dimensional, pathoanatomical data about the cerebral vasculature and also allows real-time analysis of blood flow. Contrast injections can be repeate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 38 publications
0
42
0
1
Order By: Relevance
“…Third, it is reported that BBB is affected by the injection of high concentrations, low temperatures, and repeated injections with short interval into the same blood vessel ( 14 ); therefore, during the procedure we should minimize the amount of contrast medium while keeping the image clear and pay attention to the details mentioned above. Fourth, with regard to hypertension, it is thought that the BBB is affected by a decline in the autoregulation blood vessels ( 15 ). We should control blood pressure in a reasonable range and avoid fluctuation of blood pressure during the whole perioperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Third, it is reported that BBB is affected by the injection of high concentrations, low temperatures, and repeated injections with short interval into the same blood vessel ( 14 ); therefore, during the procedure we should minimize the amount of contrast medium while keeping the image clear and pay attention to the details mentioned above. Fourth, with regard to hypertension, it is thought that the BBB is affected by a decline in the autoregulation blood vessels ( 15 ). We should control blood pressure in a reasonable range and avoid fluctuation of blood pressure during the whole perioperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that patients of an older age had poorer vascular conditions than those of a younger age, and the poor vascular condition itself can increase the risk of procedural thromboembolism, and the procedural time can be longer due to poor vascular condition [ 1 ]. Additionally, a longer procedural time can also increase the risk of procedural thromboembolism [ 17 ], because of a higher incidence of dislodging a thrombus and introducing air bubbles or hydrophilic coating materials during the procedure [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the field of neurointervention, including an MT for an AIS, procedural thromboembolism can be caused by atherosclerotic embolization from the aortic arch and adjacent large arteries, as the guiding catheters advance through the vessels [ 9 , 10 , 11 , 12 ]. Atherosclerosis of the aortic arch can be a source of procedural thromboembolism [ 5 , 12 , 13 ], and it can be assessed using a chest X-ray before the procedure [ 14 ]. We hypothesized that the aortic arch calcification (AoAC) on a chest X-ray could be related to procedural thromboembolism after an MT for an AIS.…”
Section: Introductionmentioning
confidence: 99%
“…The procedural time can be longer owing to the technical difficulties encountered during the procedure, such as advancing the guiding catheter into the carotid artery or subclavian artery [ 16 ]. Advancing a guiding catheter can be more difficult for patients with acute ischemic stroke than for those with other neurointerventional procedures, because most patients are elderly with substantial comorbidities and poor vascular health with widespread atheroma, calcification, tortuous vessels, and occlusive disease [ 17 ]. This study showed no significant difference in the total number of MT attempts between the two groups (3.38 ± 2.78 vs. 2.79 ± 2.24 times, p = 0.379); however, the procedural time was significantly different (90.9 ± 35.6 vs. 64.4 ± 33.0 min, p = 0.006) between the groups.…”
Section: Discussionmentioning
confidence: 99%